A Longitudinal study of the relationship between perceived social support and psychological well-being of adolescents from low socioeconomic status - Sayar, Melisa. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The aim of the study was to investigate the relationship between perceived social support and psychological well-being defined by - psychological adjustmentand depressive symptoms - of adolescents between ages 14-16 years old (n=237) from low socioeconomic status (SES). The study also examined the probablechanges in perceived social support and psychological well-being of adolescentsbetween two time periods, more specifically from October 2005 to May 2006 andpossible predictors of these changes in Time 1 and Time 2. Perceived Social Support Scale-Revised (Yıldırım, 2004) Personality Assessment Questionnaire (Rohner, 1971), Beck Depression Inventory (Beck, 1961)and Demographic Information Form developed by the researcher, were theinstruments of the current study. A significant relationship was found between perceived social support andpsychological adjustment both in Time 1 (r= .30, p<.01) and Time 2 (r= .23, p<.01)and between perceived social support and depressive symptoms both in Time 1(r = -.34, p<.01) and Time 2 (r= -.31, p<.01). The changes in the seven-month period demonstrated that there was asignificant decrease in perceived social support [t (236) = 4.33; p<.001] andpsychological adjustment [t (236) = 3.06; p<.01] and an increase in depressive symptoms of adolescents coming from low SES. Additionally, gender and depressivesymptoms were found to be significant predictors of perceived social support both inTime 1 and in Time 2 but not psychological adjustment.In the light of the study results, preventive counseling might be regarded as an important intervention for improving the psychological well-being of adolescentsespecially those coming from low SES.
Keywords: Adolescent psychology -- Turkey -- Social conditions.; Adolescent psychology.; Personality assessment.; Beck Depression Inventory.